TEMPAT PEMANDIAN UMUM - Charlene Vitricia; Agustinus Sutanto (Jurusan Arsitektur dan Perencanaan, 2020)
When talking about designing a 3rd place, the first question that came up was “how can we gather various people from different backgrounds, homes, and workplaces into one (same) place? Thing that drives or motivates someone to do something (in this case going to our place) is their wants and needs. Based on A theory of motivation by Abraham Maslow, individuals’ most basic needs must be met before they become motivated to achieve higher level needs. The reason behind this proposal is because currently, we’re facing a crisis of one of our physiological needs, WATER. In 2040 we’re going to lose all source of clean water in Jakarta. Even now the source of water coming from Jakarta is only 3% and the rest originated from Tangerang and Jatiluhur reservoirs. The government through the PDAM is not able to meet all the water needs in Jakarta, so that more than 40% of Jakarta citizen don’t have other choices, except using ground water which lead to another threat, land subsidence which has threatened to sink Jakarta due to groundwater exploitation and increase of high-rise buildings. Our poor water system management, and wasteful lifestyle bring us closer to the disaster for sure. This project aim to answer social needs (third place) which can be categorized at the 'third level' (in Maslow's hierarchy of motivation theory), through answering an issue of ‘lowest level of needs' first, the physiology needs through ‘Public Bath’ project. By chasing their needs we could create more potential chances for people to intersect each other and achieve the real 3rd place. AbstrakProjek ini mengangkat tema open architecture as a third place, yang kemudian memunculkan sebuah pertanyaan “Bagaimana kita dapat menyatukan beragam orang dari latar belakang yang berbeda ke suatu tempat yang sama?” Pada dasarnya, hal yang menjadi penggerak ataupun motivator bagi seseorang untuk melakukan sesuatu adalah keinginan (needs) dan kebutuhan (wants) individu itu sendiri. Berdasarkan makalah “A Theory of Motivation” dari Abraham Maslow, setiap individu cenderung memenuhi kebutuhan paling dasar sebelum memenuhi kebutuhan di tingkat atasnya. Kondisi beberapa wilayah di Indonesia, khususnya Jakarta sedang menuju krisis salah satu kebutuhan fisiologi, yaitu Air. Jakarta terancam kehilangan seluruh sumber air bersih pada tahun 2040. Bahkan saat ini sumber air yang berasal dari Jakarta hanya 3% dan sisanya berasal dari Tangerang dan waduk Jatiluhur. Pemerintah melalui PDAM tidak mampu memenuhi seluruh kebutuhan air di Jakarta, sehingga lebih dari 40% masyarakat Jakarta harus menggunakan air tanah yang kemudian menimbulkan ancaman kedua yaitu terjadinya penurunan muka tanah yang menyebabkan terancam tenggelamnya Jakarta akibat exploitasi air tanah dan meningkatnya bangunan tinggi. Proyek ini berusaha menjawab kebutuhan sosial (third place) yang dapat dikategorikan pada ‘tingkat ketiga’ (dalam teori hierarki kebutuhan Maslow), melalui penjawaban dari sebuah isu ‘kebutuhan tingkat pertama’ terlebih dahulu, yaitu kebutuhan fisiologi melalui projek ‘Tempat Pemandian Umum’. Dengan mengejar kebutuhan masyarakat, kita dapat menciptakan potensi – potensi titik pertemuan antar individu dan mencapai tempat ketiga yang sesungguhnya.